A novel subsurface adjustable dam for preventing active seawater intrusion in coastal aquifers - Chang, Qinpeng; Gao, Chenchen; Zheng, Xilai; Lin, Yucheng; Song, Xiaoran (Frontiers in Marine Science, 2024)
Subsurface physical barriers were widely used to prevent seawater intrusion in the world. After the construction of the barriers, the residual saltwater was trapped upstream due to the block. Traditional physical barriers, including cutoff walls and subsurface dams, are fixed in structure and fail in prohibiting active seawater intrusion. In this work, a novel subsurface adjustable dam, composed of dam bodies and sluice gates, was designed to prevent active seawater intrusion and store groundwater flexibly according to seasonal variations in precipitation. We set three-dimensional field-scale numerical scenarios to compare the control effects of adjustable dam, cutoff wall, and subsurface dam. The results revealed that the traditional subsurface physical barriers could mitigate the velocity of active seawater intrusion but were inadequate in completely preventing the seawater intrusion process. Furthermore, although the traditional physical barriers could temporarily alleviate the residual saltwater during the wet periods, the saltwater wedge would subsequently invade during next dry periods. Consequently, the salt mass in traditional physical barriers scenarios exhibited a gradual annual increase. In contrast, the novel subsurface adjustable dam demonstrated the ability to prevent active SWI and desalt the residual saltwater due to the construction of the dam. during the dry periods characterized by low precipitation recharge, the sluice gates were closed, effectively obstructing the path of active seawater intrusion. Conversely, during the wet periods with abundant precipitation, the sluice gates were opened, facilitating the gradual removal of the residual saltwater. This flexible adjustment mechanism of subsurface adjustable dam resulted in a consistent annual decrease in both